Hoard Of Olbian Coins Of ‘Borysthenes’ Type Found At Spring 2018 In The Region Of Gorodishche Town, Oblast Cherkassy, Ukraine - Орлик, Василий; Коцур, Виктор; Цыганенко, Лилия (Acta Archaeologica Lodziensia, 2019)
ORIGINAL TITLE: Клад ольвийских монет «борисфенов», найденный в Городищенском районе Черкасской области весной 2018 года In April 2018 an assemblage of Olbian bronze coins of Borysthenes type was found not far from the town Gorodishche, region Cherkassy, Ukraine. 52 coins were described. In opinion of authors the assemblage should be treated as the hoard.